ANALISIS FAKTOR YANG MEMPENGARUHI PERILAKU WANITA PEKERJA SEKSUAL (WPS) DALAM MENGGUNAKAN KONDOM UNTUK PENCEGAHAN HIV/AIDS DI LOKALISASI GANG SADAR BATURADEN - Retnowati, Misrina; Purwanti, Sugi (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: ANALYSIS FACTORS AFFECTING OF PROSTITUTE CONDOM USE BEHAVIOR FOR HIV/AIDS PREVENTION IN GANG SADAR PROSTITUTION Â BATURADEN. The Health Ministry Â of the Republic Indonesia said that HIV/ AIDS continues to increase until June 2014, a cumulative total 142 950 people living with HIV and AIDS reached 55 623 cases. The transmission modes of cumulative reported AIDS cases through heterosexual majority (61.5%), unknown (17.1%), IDU (15.2%), followed by transmission through prenatal (2.7%), homosexuals (2.33 %) and via blood transfusions (0.235%). Cases of HIV / AIDS can be reduced with the use of condoms during sexual intercourse. The use of condoms became one of the strategic issues in the AIDS response, including in Banyumas. The research objective was to describe the knowledge, support pimps, the availability of condom and condom use behavior. Determines the correlations of knowledge, support pimps, the availability of condom to condom use behavior. The research method was an analytic observational study with cross sectional approach. The population was all prostitute living in gang sadar some 110 people, with a sample of 50 people taken by simple random sampling. Results of the study are the majority of respondents' knowledge either 52%, the support of pimps less 66%, the availability of condoms most of exist 58%, the behavior of not using condoms most of 78%. There is a correlation Â of support pimps correlation between knowledge and the availability of condoms to condom use behavior with Ï value 0.057 and 0.666. Conclusion: there is correlation of a pimp support to the behavior of using condoms, there are no correlations between knowledge and the availability of condoms with condom use behavior. Â Keywords: pimp support, condom use behavior